209k views
0 votes
Using the distributive property, Marta multiplied the binomial (2x + 3) by the trinomial (x2 + x – 2) and got the expression below.

1 Answer

6 votes

Answer:

The resultant expression is
2x^(2)+5x^(2)-x-6.

Explanation:

The distributive property of multiplication is:


a* (b+c)=(a* b)+(a* c)

The two polynomials provided are:


(2x+3)\\(x^(2)+x-2)

Determine the final expression by multiplying the two polynomials as follows:


(2x+3)* (x^(2)+x-2)=[2x*(x^(2)+x-2)]+[3*(x^(2)+x-2)]


=[(2x* x^(2))+(2x* x)-(2x* 2)]+[(3* x^(2))+(3* x)-(3* 2)]\\\\=[2x^(3)+2x^(2)-4x]+[3x^(2)+3x-6]\\\\=2x^(3)+2x^(2)+3x^(2)-4x+3x-6\\\\=2x^(3)+5x^(2)-x-6

Thus, the resultant expression is
2x^(2)+5x^(2)-x-6.

User TheMadKing
by
5.2k points